Nursing intervention to prevent delirium in critically ill adults - Claudia Consuelo Torres Contreras; Astrid Nathalia Páez-Esteban; Mayerli Katherine Rincon-Romero; Raquel Rivera Carvajal; Marisela Márquez Herrera; Alfredo Hinestrosa Díaz del Castillo (SciELO, 2021)
ABSTRACT Objective: To determine the effectiveness of a nursing intervention for delirium prevention in critically ill patients. Method: A quasi-experimental study was conducted with a non-equivalent control group and with evaluation before and after the intervention. 157 Patients were part of the intervention group and 134 of the control group. Patients were followed-up until they were discharged from the ICU or died. The incidence of delirium in both groups was compared. Additionally, the effect measures were adjusted for the propensity score. Results: The incidence and incidence rate of delirium in the control group were 20.1% and 33.1 per 1000 person-days (CI 95% 22.7 to 48.3) and in the intervention group was 0.6% and 0.64 per 1000 person-days (CI 95% 0.22 to 11.09), respectively. The crude Hazard Ratio was 0.06 (CI 95% 0,008 to 0,45) and adjusted 0.07 (CI 95% 0,009 to 0,60). The number needed to be treated was six. Conclusion: Low incidence of delirium in critically ill patients intervened demonstrated the effectiveness of interventions. The average intervention time was 4 days with a 15-minutes dedication for each patient.